2009
DOI: 10.4067/s0717-92272009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Bruxómanos presentan un estilo de personalidad distintivo

Abstract: Introducciónl concepto tanto de salud y enfermedad ha ido evolucionando desde un modelo biomédico, que centraba el diagnóstico y tratamiento de la enfermedad en los aspectos fisiológicos y patofisiológicos del cuerpo humano 1-3 , hacia un modelo biopsicosocial 4 , en el cual se señala que toda enfermedad es de naturaleza multifactorial enfatizando la participación de factores psicoló-gicos en el proceso de enfermar.Diversos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…Three of these scales (Pleasure-Enhancing, Sensing and Feeling-Guided) showed high means in our study. However, in a study by Moncada et al (2009) on variables associated with bruxism, Pain-Avoiding, Withdrawing, Submissive and Cooperative, only Cooperative is in agreement with our study, insomuch as it showed the highest mean of all the personality scales.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Three of these scales (Pleasure-Enhancing, Sensing and Feeling-Guided) showed high means in our study. However, in a study by Moncada et al (2009) on variables associated with bruxism, Pain-Avoiding, Withdrawing, Submissive and Cooperative, only Cooperative is in agreement with our study, insomuch as it showed the highest mean of all the personality scales.…”
Section: Discussionsupporting
confidence: 92%
“…The authors used six MIPS scales, Pleasure-Enhancing, Internally Focused, Sensing, Feeling-Guided, Withdrawing and Submissive, which explained 36% of the variance, and participants with a physical illness scored higher than the general population. Moncada et al (2009) also applied the MIPS in a study on bruxism, and found significant differences between groups with and without that disorder. In that study, subjects without bruxism showed a more adaptive personality profile.…”
Section: Introductionmentioning
confidence: 99%
“…Entre el 5% -20 % de la población en términos medios está afectada de bruxismo si se utiliza para su determinación un cuestionario, o bien si el sujeto es interrogado acerca de si es consciente de que rechina los dientes. Sin embargo, si la incidencia del bruxismo se determina por signos directos exploratorios, el porcentaje es mucho más alto (7,9).…”
Section: Prevalencia General Del Bruxismounclassified
“…-Dolores crónicos como ser otitis a repetición (7,9) La clasificación de En el área de las metas motivacionales los bruxistas tienden a experimentar la vida de modo pesimista mientras los no bruxistas buscan obtener refuerzo positivo y tienden a experimentar los sucesos de la vida de modo optimista. A su vez los no bruxistas intentan modificar activamente los acontecimientos del entorno y toman en cuenta sus propios puntos de vista para sus decisiones.…”
Section: Entre Estos Se Pueden Distinguirunclassified